Residents preferences associated with tax amnesty program predisposition - Prasojo, Prasojo; Syarifah, Lailatis (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Purpose - The purpose of this study is to determine the motivation of taxpayers to take part in tax amnesty so that it is expected to be able to evaluate the implementation of tax amnesty that has been carried out by the Indonesian government in 2016-2017 and provide empirical evidence on the implementation of the tax amnesty program to support the stick and carrot theory in the implementation of taxation in Indonesia.Method - The methodology used in this research is a case study. Interviews are used to collect data and are supported by secondary data from sites, web, and documents.Result - The results of this study indicate that the reasons for many taxpayers to join this program were because it is beneficial for the country and avoid the risk of administrative sanctions (fines and interest) as well as audits. The reason for taxpayers who did not participate in this program was because they did not have other assets that had not been reported in the tax return.Implication - The implication of this study is to determine the motivation of taxpayers to take part in tax amnesty so that it is expected to be able to evaluate the implementation of tax amnesty. At the same time, that has been carried out by the Indonesian government in 2016-2017 and provides empirical evidence on the implementation of the tax amnesty program to reason action and social learning theory in the implementation of taxation in Indonesia.Originality - This study explores information from regulators (tax officials) and taxpayers, both those who do and who do not participate in tax amnesty, which is rarely done by other researchers.